Inter/intra-tumoral dose response variations assessed using FDG-PET/CT feedback images: Impact on tumor control and treatment dose prescription. (January 2021) - Yan, Di; Chen, Shupeng; Krauss, Daniel J.; Deraniyagala, Rohan; Chen, Peter; Ye, Hong; Wilson, George
Highlights: Tumor DRM assessed using the feedback images has similar distribution to those of in vitro clonogenic assay. Inter-tumoral variations of baseline SUV and DRM were quite different between the HPV− and HPV+ tumor group. However, intra-tumoral variations of both tumor groups were similar and large. The inter/intra-tumoral variations cause very large heterogeneity on the individual tumor controls. Heterogeneous dose prescription guided adaptively using metabolic imaging feedback shows a clear advantage. Abstract: Purpose: To quantify inter/intra-tumoral variations of baseline metabolic activity and dose response. To evaluate their impact on tumor control and treatment dose prescription strategies. Methods and materials: Tumor voxel baseline metabolic activity, SUV 0, and dose response matrix, DRM, quantified using the pre-treatment and weekly FDG-PET/CT imaging feedback for each of 34 HNSCC patients (25 HPV+ and 9 HVP−) were evaluated. Inter/intra-tumoral variations of tumor voxel ( SUV 0, DRM ) for each of the HPV− and HPV+ tumor groups were quantified and used to evaluate the variations of individual tumor control probabilities and the efficiency of uniform vs non-uniform treatment dose prescription strategies. Results: Tumor voxel dose response variation of all tumor voxels assessed using FDG-PET/CT imaging feedback had the mean(CV) = 0.47(47%), which was consistent with those of previously published in vitro tumor clonogenic assay. The HPV− tumors had the mean(CV) dose response, 0.53(49%), significantly larger than those of the HPV+ tumors, 0.45(43%). However, their baseline SUVs were opposite, 6.5(56%) vs 7.7(65%). Comparing to the inter-tumoral variations, both HPV−/+ tumor groups showed larger intra-tumoral variations, (53%, 58%) vs (20%, 31%) for the baseline SUV and (38%, 37%) vs (31%, 21%) for the dose response. Due to the large dose response variations, treatment dose to control the tumor voxels has very broad range with CV of TCD 50  = 97% for the HPV− and 67% for the HPV+ tumor group respectively. As a consequence, heterogeneous prescription dose could potentially reduce the treatment integral dose for 92% of the HPV+ tumors and 78% of the HPV− tumors. Conclusions: The study demonstrates that tumor dose response assessed using FDG-PET/CT feedback images had a similar distribution to those assessed conventionally using in vitro tumor clonogenic assay. Inter-tumoral dose response variation seems larger for HPV− tumors, but intra-tumoral dose response variations are similar for both HPV groups. These variations cause very large variation on the individual tumor control probability and limit the efficacy of dose escalation and de-escalation in conventional clinical practice. On the other hand, heterogeneous dose prescription guided by metabolic imaging feedback has a potential advantage in radiotherapy.